Open risk assessment: data. (June 2016) - Gilsenan, Mary B.; Abbinante, Fabrizio; O'Dea, Eileen; Canals, Ana; Tritscher, Angelika
Abstract: Since its foundation, EFSA and the Member States have made significant progress in the area of data collection for risk assessment and monitoring. In partnership with competent authorities and research organisations in the Member States, EFSA has become a central hub of the European data on food consumption, chemical occurrence and foodborne outbreaks. Beyond EFSA's use of these data and sharing of contaminants and food consumption data with the World Health Organization and the Food and Agriculture Organization to support international risk assessment, they remain largely unexploited. In addition, for some of its risk assessments, EFSA also relies on published information, as well as on scientific studies sponsored and submitted by industry. The environment in which the Authority operates has significantly evolved since its foundation. The growth of digital technology has granted scientists and consumers alike faster and more efficient access to data and information. The open data movement, which has entered the sphere of the European Union institutions, is unleashing the potential for reuse of data. In parallel, the work of EFSA is increasingly subject to demands for more openness and transparency across its spectrum of stakeholders. EFSA aims to enhance the quality and transparency of its outputs by giving access to data and promoting the development of collaborative platforms in Europe and internationally. EFSA also plans to work with data providers and organisations funding research to adopt open data concepts and standards; gaining better access to, and making better use of, data from a wider evidence base. During the breakout session on 'Open Risk Assessment: Data' at the EFSA 2nd Scientific Conference 'Shaping the Future of Food Safety, Together' (Milan, Italy, 14–16 October 2015) opportunities and challenges associated with open data, data interoperability and data quality were discussed by sharing experiences from various sectors within and outside EFSA's remit. This paper provides an overview of the presentations and discussions during the breakout session.